2013
DOI: 10.1161/circresaha.112.276519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intracoronary CD34 + Stem Cell Transplantation in Nonischemic Dilated Cardiomyopathy Patients

Abstract: Objective: We investigated long-term effects of intracoronary CD34+ cell transplantation in dilated cardiomyopathy and the relationship between intramyocardial cell homing and clinical response. Methods and Results:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
220
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 256 publications
(246 citation statements)
references
References 30 publications
13
220
0
12
Order By: Relevance
“…In patients with DCM, coronary flow reserve is often impaired both globally and regionally because of impaired vasculogenesis and angiogenesis 20, 21. In our previous clinical studies in DCM, CD34 + cell therapy was associated with a significant improvement in myocardial perfusion as assessed by SPECT 5, 22. Interestingly, although the majority of changes occurred in the myocardial segments targeted with stem cell injections, some improvement in perfusion occurred also in the remote nontargeted areas, suggesting that a paracrine component may play an important role.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In patients with DCM, coronary flow reserve is often impaired both globally and regionally because of impaired vasculogenesis and angiogenesis 20, 21. In our previous clinical studies in DCM, CD34 + cell therapy was associated with a significant improvement in myocardial perfusion as assessed by SPECT 5, 22. Interestingly, although the majority of changes occurred in the myocardial segments targeted with stem cell injections, some improvement in perfusion occurred also in the remote nontargeted areas, suggesting that a paracrine component may play an important role.…”
Section: Discussionmentioning
confidence: 96%
“…Disease progression in DCM affects both ventricles, and right ventricular (RV) dysfunction represents an important adverse prognostic factor 2, 3. Although several clinical trials have demonstrated that left ventricular dysfunction in DCM can be partially reversed by cell therapy 4, 5, 6, 7, no study to date investigated the effects of this approach on RV. Thus, the aim of the present study was to investigate the effects of transendocardial CD34 + cell therapy on RV function in patients with DCM.…”
Section: Introductionmentioning
confidence: 99%
“…27 Cell therapy of CD34 + cells into non-ischemic dilated cardiomyopathy patients, still resulted in a 6% increase in left ventricle stroke volume but with no difference in sudden cardiac death rates during treatment from the control group. 28 This modest progress in stem cell injection therapy is attributed to the harsh proinflammatory environment of the scarred myocardium, and the stiff substrate of increased collagen deposition and crosslinking that is incapable of allowing full stem cell engraftment. 16,29,30 Before the introduction of stem cell injections into the myocardium, surgeons have been and still are replacing the scarred myocardium completely with the Dor or left ventricle remodeling procedure.…”
Section: 18mentioning
confidence: 99%
“…Se encuentra en 67 . En pacientes con miocardiopatía de etiología no isquémica, existe una experiencia más reducida [68][69][70][71][72][73][74][75] . El ensayo aleatorizado ABCD señaló un aumento significativo y persistente de la FEVI y mejora en la calidad de vida en pacientes con cardiopatía dilatada, tratados con BMMC autólogas en su seguimiento a 3 años 72 .…”
Section: Terapia Celular En Cardiopatías Crónicasunclassified
“…El ensayo aleatorizado ABCD señaló un aumento significativo y persistente de la FEVI y mejora en la calidad de vida en pacientes con cardiopatía dilatada, tratados con BMMC autólogas en su seguimiento a 3 años 72 . Otro estudio aleatorizado recientemente publicado, también reveló un aumento persistente de la FEVI, así como una reducción significativa de la morbimortalidad en pacientes tratados con células BMMC autólogas, a 60 meses 74 . En nuestro ensayo clínico controlado en pacientes con cardiopatía dilatada, también se evidenció una mejoría significativa y persistente de la capacidad funcional, documentándose adicionalmente un aumento de la FEVI a partir de los 6 meses de tratamiento (26,75 ± 4,85 a 37,82 ± 6,97%, p = 0,001), en los pacientes infundidos con BMMC 75 .…”
Section: Terapia Celular En Cardiopatías Crónicasunclassified